2018
DOI: 10.1155/2018/2403802
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture and Characterization of Mucoadhesive Buccal Films Based on Pectin and Gellan Gum Containing Triamcinolone Acetonide

Abstract: The treatment of canker sores can be quite compromised by the short period of the drug in the place of action. In this context, there is a need to develop drug dosage forms that allow more contact with the oral mucosa providing prolonged drug release. Therefore, the aim of this work was to obtain and characterize buccal films based on pectin and gellan gum in order to evaluate the potential use of these natural polymers in the production of pharmaceutical dosage forms for controlled release of TA in the oral m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Our results were in close agreement with the previously published study where gellan gum-based buccal films showed similar thermal decomposition of polymer. 61
Figure 6 DSC thermogram of Mox, blank film, and GG3.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were in close agreement with the previously published study where gellan gum-based buccal films showed similar thermal decomposition of polymer. 61
Figure 6 DSC thermogram of Mox, blank film, and GG3.
…”
Section: Resultsmentioning
confidence: 99%
“… 66 Moreover, hydrophilic groups in gellan gum such as hydroxyl and carboxylic groups bind with the mucin through hydrogen bonding to facilitate mucoadhesion. 61 This prolongs the retention of films in the oral cavity by resisting the wash off effect of saliva and mastication forces for controlled release of actives.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the interactions occurring between the particles of the hydrophilic polymers are sufficient to obtain API extended-release carriers without the use of potentially harmful cross-linking agents and organic solvents. The Korsmeyer–Peppas model was used to describe the release kinetics of triamcinolone acetate from the films, pointing to drug diffusion following Fick’s law as the mechanism for the release of the substance from the engineered films [ 47 ].…”
Section: Carriers and Biodegradable Polymeric Materials In Dentistrymentioning
confidence: 99%
“…The glass slide was placed in the bottom of the dissolution vessel, which was later filled with 900 ml of simulated saliva (phosphate buffer, pH 6.8) maintained at 37±1 °C; the paddle was rotated at 50 rpm. Samples of dissolution medium were withdrawn at predetermined time intervals, filtered, and analyzed by UV Spectrophotometry after suitable dilution [28]. To maintain sink conditions the samples were replaced with equal volumes of fresh buffer.…”
Section: Measurement Of Ex Vivo Mucoadhesive Strengthmentioning
confidence: 99%